The devil's ransom - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2023)
When his covert company, along with every other entity in the Taskforce, is hit with a ransomware attack linked to the Taliban, Pike must stop a plot to alter the balance of power on the global stage orchestrated by a former NSA specialist in the U.S. government.